Maternal chewing improves prenatal stress-induced cognitive deficit and anxiety-like behavior associated with alterations of the apoptotic response and serotonin pathway in mouse offspring. (October 2021) - Kajimoto, Kyoko; Hisada, Chie; Ochi, Suzuko; Yoshikawa, Eri; Suzuki, Ayumi; Tsugane, Hiroko; Zhang, Jiahe; Iinuma, Mitsuo; Kubo, Kin-ya; Azuma, Kagaku
Highlights: Prenatal stress induced hippocampal neuronal apoptotic response. Prenatal stress downregulated central serotonin expression. Chewing alleviated prenatal stress-induced apoptosis response. Chewing ameliorated prenatal stress-induced decreased serotonin level. Chewing improved prenatal stress-induced cognitive impairment and anxiety behavior. Abstract: Objective: To examine whether maternal chewing affects prenatal stress-induced behavioral alternations associated with the changes in apoptosis-related proteins and serotonin pathway of the mouse offspring. Design: Pregnant mice were assigned to control, stress, and stress/chewing groups. Stress mice were placed in restraint tubes, from gestational day 12 until parturition. Stress/chewing mice were given a wooden stick for chewing during stress period. Morris water maze and hole-board tests were applied for behavioral alterations in one-month-old male pups. Hippocampal mRNA expression of B-cell lymphoma 2 (Bcl-2) and Bcl-2 associated X protein (Bax) was analyzed by quantitative real-time PCR. Serotonin and tryptophan hydroxylase expression level in the dorsal raphe nucleus was investigated immunohistochemically. Results: Prenatal stress impaired the spatial learning, induced anxiety-like behavior, increased the ratio of hippocampal Bax/Bcl-2 expression, and decreased the expression of serotonin and tryptophan hydroxylase in dorsal raphe nucleus of the offspring. Maternal chewing ameliorated prenatal stress-induced cognitive impairment, anxiety-like behavior, and attenuated the increased ratio of hippocampal Bax/Bcl-2 expression, and the downregulated serotonin signaling in dorsal raphe nucleus of the offspring. Conclusions: Our results indicate that maternal chewing could improve prenatal stress-related anxiety-like behavior and cognitive impairment in mouse offspring, at least in part by affecting hippocampal apoptotic response and central serotonin pathway.